IMPROVING VOCABULARY MASTERY USING INSTAGRAM POLLING QUIZ FOR ELEVENTH GRADE STUDENTS AT SMKN 1 NGANJUK - Yuli Antika Nurhayati; Caltira Rosiana (Universitas PGRI Mpu Sindok, 2025)
Background: The objectives of this study are, (1) to identify the challeenges of students' vocabulary mastery before using Instagram poll quiz for eleventh grade at SMKN 1 Nganjuk, (2) to analyze the development of students' vocabulary mastery after using Instagram poll quiz for eleventh grade at SMKN 1 Nganjuk, (3) to identify the significant difference between students' vocabulary mastery before and after using Instagram poll quiz as English learning media for eleventh grade at SMKN 1 Nganjuk. This research design uses a quantitative approach and this type of research is Quasi Experiment. This research design is pre-test and post-test (one group pre-test and post-test). The population of this research is grade XI students at SMKN 1 Nganjuk in the academic year 2023/2024. The sample of this study were students of class XI-PGIM 2. The sampling technique used convenience sampling technique. Based on the written test scores, students obtained an average pre-test score of 57 students with a classification of